LEADERSHIP, WORK SPIRITUALITY, COMPETENCE AND LOYALTY TO EMPLOYEE PERFORMANCE - ADIPUTRA, PUTU DONNY NOVARIANA (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
This study aims to analyze the role of leadership, work spirituality, competence, and loyalty to employee performance. The respondents involved were 86 employees who worked at PT. Bank Pembangunan Daerah Bali Karangasem Branch. The study was conducted by census. This study employed descriptive analysis to determine the number, percentage, and average of respondents? answers. Additionally, this study also used inferential analysis by evaluating the measurement model (outer model) and the structural model (inner model). The results indicate that leadership had a positive and significant effect on job satisfaction and employee performance. Leadership and spirituality had a positive and significant influence on work loyalty. Besides, competence and loyalty had a positive and significant effect on employee performance. However, in this study, competence, leadership, and spirituality did not show a significant effect on employee performance.